The Influence of Current Ratio, Debt To Equity Ratio and Net Profit Margin on Company Value with Company Size as a Moderating Variable in the Financial Sector for the 2020-2022 Period - Noni Septia; Dedi Hariyanto (UNIVED Press, 2024)
This research aims to determine the effect of CR, DER, and NPM on company value with company size as a moderating variable in the financial sector for the 2020-2022 period. The population used in this research is the financial sector on the Indonesia Stock Exchange (BEI) for the 2020-2022 period. This type of research is quantitative. Secondary data and purposive sampling techniques were used in data collection and sampling techniques with multiple linear analysis. Using SPSS 24. The research results of CR and DER have no influence on company value, while NPM has an influence on company value. And company size does not moderate DER and NPM on company value, while CR can be moderated by company size on company value.